Decision-making regarding immediate vs. interval postpartum levonorgestrel intrauterine device insertion timing - Abigail Davenport; Laura Morello; Kavita Shah Arora (BMC, 2023)
Abstract Background Understanding decision-making for contraception initiation timing postpartum may help guide patients in selecting a contraceptive method most aligned with their reproductive goals. The objective of this study was to explore the decision-making process in patients who chose immediate postplacental (IPP) levonorgestrel intrauterine device (LNG IUD) insertion versus interval insertion at the postpartum follow-up visit. Methods We recruited English-speaking, reproductive-aged adult postpartum participants who received either an IPP or interval postpartum LNG IUD from September to December 2017 at MetroHealth Medical Center. We conducted interviews over the phone utilizing a pilot-tested, semi-structured interview guide. Interview topics included past experiences with contraception, provider counseling, intrapartum factors, and current experiences after IUD insertion. Results We interviewed 20 participants (12 IPP and eight interval IUD recipients). Participants receiving an IPP IUD described convenience, desire for immediate contraception, pain control and availability of alternative contraception options as influential for their decision. Patients who received an interval IUD performed outside research, focused on the events surrounding delivery, and generally favored additional recovery time before obtaining an IUD. Patients who received interval IUDs were often not aware that IPP IUDs were available. Early, frequent, and comprehensive counseling was viewed favorably when compared to counseling upon arrival to the laboring unit. While overall there was congruence of participant expectations and experiences, unexpected expulsion affected desire for future IUD use in some participants. Conclusion Providers should be mindful that prior experience and knowledge as well as delivery room considerations affect insertion timing decision-making. Trial registration N/A